2016
DOI: 10.5194/bg-13-3869-2016
|View full text |Cite
|
Sign up to set email alerts
|

Simulating oxygen isotope ratios in tree ring cellulose using a dynamic global vegetation model

Abstract: Abstract. Records of stable oxygen isotope ratios in tree rings are valuable tools to reconstruct past climatic conditions and investigate the response of trees to those conditions. So far the use of stable oxygen isotope signatures of tree rings has not been systematically evaluated in dynamic global vegetation models (DGVMs). DGVMs integrate many hydrological and physiological processes and their application could improve proxy-model comparisons and the interpretation of oxygen isotope records. Here we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 104 publications
1
36
0
Order By: Relevance
“…However, these assumptions cannot be tested with our data. Finally, the fraction of oxygen exchange between carbohydrates and water at the site of cellulose synthesis may vary from a species to another (e.g., Sternberg & Ellsworth, ). A lower fraction induces a higher δ 18 O in cellulose, and relatively small changes in the exchange rate have a significant impact on the isotopic composition (e.g., 10% change induced 1.9‰ variation in the δ 18 O of some cellulose according to Keel et al, ). Song et al () and Li et al () both suggested that the 18 O enrichment of pine species compared to oak species ( Pinus rigida versus Quercus velutina and Quercus prinus and Pinus densiflora versus Quercus serrate and Quercus variabilis ) could reveal a lower fraction of oxygen exchange.…”
Section: Discussionmentioning
confidence: 99%
“…However, these assumptions cannot be tested with our data. Finally, the fraction of oxygen exchange between carbohydrates and water at the site of cellulose synthesis may vary from a species to another (e.g., Sternberg & Ellsworth, ). A lower fraction induces a higher δ 18 O in cellulose, and relatively small changes in the exchange rate have a significant impact on the isotopic composition (e.g., 10% change induced 1.9‰ variation in the δ 18 O of some cellulose according to Keel et al, ). Song et al () and Li et al () both suggested that the 18 O enrichment of pine species compared to oak species ( Pinus rigida versus Quercus velutina and Quercus prinus and Pinus densiflora versus Quercus serrate and Quercus variabilis ) could reveal a lower fraction of oxygen exchange.…”
Section: Discussionmentioning
confidence: 99%
“…The mixing term ranges from 0 to 1 and describes the efficiency with which isotopic exchange between photosynthates and xylem water occurs during cellulose metabolism. This model and close variants have been used in numerous studies and we refer readers to Roden et al (); Barbour et al (); Evans (); Ogée et al (); Keel et al () and references therein for additional details.…”
Section: Methodsmentioning
confidence: 99%
“…To solve for normalΔleaf in equation , the modeled estimates of transpiration, photosynthesis, leaf temperature, leaf VPD, and canopy conductances from SCOPE were passed through Supplementary equations 1‐10 (Barbour et al, ; Keel et al, ; Ogée et al, ; Roden et al, ). The cellulose model also required estimates of the path length of the leaf, which was set at a fixed value of 0.01 cm (Keel et al, ), and the exchange efficiency between xylem water and sugars during cellulose metabolism (i.e., pe ), which was set at 0.42 (Roden et al, ). The model produced 30‐minute estimates of the isotopic ratio of cellulose for all time‐steps when photosynthesis was greater than 0 and the air temperature was above the critical threshold for xylogenesis (Rossi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The LPX‐Bern 1.3 model (Keel et al, ; Keller et al, ; Spahni et al, ; Stocker et al, ) was developed from LPJ model. The LPX‐Bern model uses the same annual allocation scheme and allometric equations as LPJ model.…”
Section: Methodsmentioning
confidence: 99%